Absorption spectra and crystal chemistry of quartz implanted with cobalt ions - A. I. Bakhtin; A. V. Mukhametshin; O. N. Lopatin; V. F. Valeev; V. I. Nuzhdin; R. I. Khaibullin (Известия высших учебных заведений: Геология и разведка)
Background. High-dose implantation of cobalt ions into the crystal structure of natural colourless quartz was carried out. Samples of crystal plates of rock crystal from the Svetlinskoye deposit in the South Urals plane-parallel were studied. All samples were crystallographically oriented perpendicular to the symmetry axis of the third order. Cobalt implantation into quartz was carried out using an ILU-3 ion-beam accelerator along the С axis of symmetry.Aim. To determine the ranges of thermal annealing for a controlled change in the sample colour and to establish the crystal-chemical features of the changes occurring in quartz matrix due to ionbeam modification of mineral properties.Materials and methods. Implantation modes included: room temperature, residual vacuum 10–5 torr, radiation dose from 1.0×1017 to 1.5×1017 ion/cm2 at a constant ion current density of 10 μA/cm2. Post-implantation heat treatment was carried out in three stages. The control of crystallochemical changes was carried out using a highly sensitive spectrophotometer with a wide range of wavelengths.Results. It was found that the revealed absorption bands are associated with electronic transitions in cobalt ions (Со2+ and Со 3+) coordinated in the crystal matrix of implanted and heat-treated rock crystal. The formation of an independent ultradispersed spinel phase in the irradiated quartz matrix was confirmed. The newly formed phase belongs to a partially reversed cobalt spinel.Conclusions. Taking into account the quantum-optical properties of cobalt spinel (laser shutters), the method of ion-beam modification of mineral crystal structures, quartz in particular, is highly promising in terms of creating new composite materials based on natural and artificial mineral raw materials.